Biological activities of non-enzymatic oxygenated metabolites of polyunsaturated fatty acids (NEO-PUFAs) derived from EPA and DHA: New anti-arrhythmic compounds?. (December 2018) - Galano, Jean-Marie; Roy, Jérôme; Durand, Thierry; Lee, Jetty Chung-Yung; Le Guennec, Jean-Yves; Oger, Camille; Demion, Marie
Abstract: ω3 Polyunsaturated fatty acids (ω3 PUFAs) have several biological properties including anti-arrhythmic effects. However, there are some evidences that it is not solely ω3 PUFAs per se that are biologically active but the non-enzymatic oxygenated metabolites of polyunsaturated fatty acids (NEO-PUFAs) like isoprostanes and neuroprostanes. Recent question arises how these molecules take part in physiological homeostasis, show biological bioactivities and anti-inflammatory properties. Furthermore, they are involved in the circulations of childbirth, by inducing the closure of the ductus arteriosus . In addition, oxidative stress which can be beneficial for the heart in given environmental conditions such as the presence of ω3 PUFAs on the site of the stress and the signaling pathways involved are also explained in this review.